Residual displacement estimation for soft soils: Application to Mexico city lake-bed. Issue 130 (March 2020) - Quinde, Pablo; Terán-Gilmore, Amador; Reinoso, Eduardo
Abstract: Current seismic regulations do not assess the seismic performance of structures during a given seismic event, and therefore do not require an estimation of their residual displacement or level of structural damage. Nevertheless, this information is relevant after intense ground motions to assess the possibility of re-occupying a building. This paper develops simple expressions to estimate the maximum displacement demand from the residual displacement of single-degree-of-freedom systems subjected to long-duration narrow-banded ground motions generated in soft soil sites (particularly, those located in Mexico City). To overcome the limited scope of previous studies, more than 35, 000 seismic simulations were performed. The influence of the lateral strength of the single-degree-of-freedom systems is considered. A simplified relation between the residual and maximum displacement demands is established. Highlights: This study estimate the maximum displacement demand from the residual displacement. Study subjected to long duration narrow-banded ground motions generated in soft soil sites. The influence of the lateral strength of systems is considered in estimations. The proposed model reasonable estimates the actual residual displacements.